(untitled) (Tamaddun, 2018)
Writing as a productive activity for high school students can provide many benefits, such as developing creativity, instilling courage and self-confidence, organizing and clarifying thoughts, ways of thinking, intelligence, and emotional sensitivity of students. The many benefits can be obtained in learning to write, the writing activity should be one of the activities that students like. The researcher has an idea to conduct research with the title "Improving the Learning of Writing Persuasion Essay by Applying Example-Based Learning Model (Example Non Examples) Class X Students of SMA Negeri 1 Awangpone Kab. Bone ". The problem was examined to overcome the problem of learning to write persuasion in class X SMA Negeri 1 Awangpone which is categorized as low. This type of research includes Classroom Action Research which aims to improve the learning of writing persuasion writing by applying an example-based learning model (example non examples) of class X students of SMA Negeri 1 Awangpone Kab. Bone. This class action research was conducted in two cycles, each of which was carried out through four stages, namely planning, implementing, observing, and reflecting. Cycle II was carried out as an implementation of action which was an improvement in learning from cycle I. The results of this study also showed a significant improvement in the learning process and in learning outcomes. The classroom atmosphere seems conducive and students appear more enthusiastic and motivated to participate in learning, cooperate with each other in groups and appear to be active in writing persuasion essays.